2021
DOI: 10.1002/deo2.83
|View full text |Cite
|
Sign up to set email alerts
|

Fever and electrocoagulation syndrome after colorectal endoscopic submucosal dissection for patients with immunosuppressants and steroids

Abstract: Objectives Transient fever and electrocoagulation syndrome after colorectal endoscopic submucosal dissection (ESD) remain a challenge. The aim of this study was to assess the risk factors of post‐ESD fever and post‐ESD coagulation syndrome (PECS), focusing on the involvement of immunosuppressive drugs and steroids (IM). Methods This retrospective analysis included 510 patients who underwent colorectal ESD at Okayama University Hospital from 2015 to 2020. The incidence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…They speculated that the wall of the cecum was so stretchable that heat after electrocoagulation would extend more easily to the muscularis propria. In addition, other studies reported that female sex, 9,27–29 submucosal fibrosis, 10,27 and long procedure time 8,17,28 and the use of immunosuppressants or steroid 17 were risk factors for PECS in colorectal ESD. Of note, female sex was commonly identified as an independent risk factor for PECS in many studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They speculated that the wall of the cecum was so stretchable that heat after electrocoagulation would extend more easily to the muscularis propria. In addition, other studies reported that female sex, 9,27–29 submucosal fibrosis, 10,27 and long procedure time 8,17,28 and the use of immunosuppressants or steroid 17 were risk factors for PECS in colorectal ESD. Of note, female sex was commonly identified as an independent risk factor for PECS in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, female sex was also identified as a risk factor for PECS in addition to long procedure time and large specimen size. Yamamoto et al 17 reported that injury to the muscle layer was an independent risk factor for PECS after colorectal ESD. However, there was no clear definition of injury to the muscle layer, and the relationship between the grade of the injury to the muscle layer and PECS was not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations